2021
DOI: 10.1186/s13148-021-01024-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiles of bronchoscopic biopsies for the diagnosis of lung cancer

Abstract: Background Lung cancer is the leading cause of cancer-related death in most western countries in both, males and females, accounting for roughly 20–25% of all cancer deaths. For choosing the most appropriate therapy regimen a definite diagnosis is a prerequisite. However, histological characterization of bronchoscopic biopsies particularly with low tumor cell content is often challenging. Therefore, this study aims at (a) determining the value of DNA methylation analysis applied to specimens ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…To test the stability and extendibility, we applied this computational framework to external data from NCBI Gene Expression Omnibus (GEO) database, under accession GSE90496 [31], GSE155207 [32], GSE158075 [33], and GSE164988. The brain tumours DNA methylation dataset (GSE90496) includes 2801 samples, meanwhile 294 of these samples (294/2801) were selected out, the disease stage of which is initially operation, the age distributed in range of 25 to 70, and the WHO grade is I, II or III.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the stability and extendibility, we applied this computational framework to external data from NCBI Gene Expression Omnibus (GEO) database, under accession GSE90496 [31], GSE155207 [32], GSE158075 [33], and GSE164988. The brain tumours DNA methylation dataset (GSE90496) includes 2801 samples, meanwhile 294 of these samples (294/2801) were selected out, the disease stage of which is initially operation, the age distributed in range of 25 to 70, and the WHO grade is I, II or III.…”
Section: Resultsmentioning
confidence: 99%
“…GSE155207 [32], GSE158075 [33], and GSE164988. The brain tumours DNA methylation dataset (GSE90496) includes 2801 samples, meanwhile 294 of these samples (294/2801) were selected out, the disease stage of which is initially operation, the age distributed in range of 25 to 70, and the WHO grade is I, II or III.…”
Section: External Validation With Tissue Dna Methylation Datamentioning
confidence: 99%
“…However, considerable progress has been made with different methods to diagnose lung cancer. The diagnostic accuracy of lung cancer was 97.3% when some scholars studied the lung cancer tissue sections under weak supervision [ 47 , 48 ]. It clearly demonstrates that this four-differentially expressed MMRG-signature model has great potential for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A study of breast tissue from healthy women found differences in PM20D1 methylation according to ethnic origin [97] . Additionally, in an epigenome-wide association study for COVID-19 severity, the PM20D1 gene was found to be differentially methylated [98] .…”
Section: Other Phenotypesmentioning
confidence: 99%